Ownership Structure, Board Size, and Carbon Emission Disclosures: Empirical Evidence from ASEAN-5 Countries - Lina, Lina; Rohmah, Faizah Syifa (Jurnal Dinamika Akuntansi dan Bisnis, 2024)
This study aims to investigate the influence of institutional ownership structure and managerial ownership on corporate carbon emissions disclosure in ASEAN-5 with the size of the board of commissioners as a moderator. Large-cap companies listed on each ASEAN-5 countries stock exchange were selected as research samples. The sample companies have published sustainability reports and integrated annual reports that disclose carbon emissions between 2018 and 2022 (175 company-year observation). Using multiple linear regression analysis, this study found that institutional ownership and managerial ownership have a negative impact on carbon emissions disclosure. The role of board of commissioner size was found weakening the negative relationship between institutional ownership and managerial ownership on carbon emissions disclosure.